Effects of Trichoderma harzianum biofertilizer on growth, yield, and quality of Bupleurum chinense - Li Liu; Yuansong Xu; Hailu Cao; Ya Fan; Kan Du; Xun Bu; Demin Gao (Plant Direct, 2022)
Abstract The use of chemical fertilizers and pesticides led to a decline in the quality and yield of Bupleurum chinense. The aim of this study was to determine the effects of Trichoderma harzianum biofertilizer on the growth, yield, and quality of radix bupleuri and microbial responses. The results showed that T. harzianum biofertilizer promoted the growth of B. chinense and increased the yield and quality of radix bupleuri. In addition, it increased the contents of NH4+–N, NO3−–N, available K, and available P and increased the activities of sucrase and catalase in the rhizosphere soil. High‐throughput analysis showed that the dominant bacteria in the rhizosphere were Proteobacteria (28%), Acidobacteria (23%), and Actinobacteria (17%), whereas the dominant fungi were Ascomycota (49%), Zygomycota (30%), and Basidiomycota (6%). After the application of T. harzianum biofertilizer, the abundance of Proteobacteria and Actinobacteria (relative to total bacteria) and Ascomycota and Basidiomycota (relative to total fungi) increased, but the relative abundance of Acidobacteria decreased. Canonical correlation analysis (CCA) showed that the relative abundance of Pseudarthrobacter, Streptomyces, Rhizobium, Nocardioides, Minimedusa, and Chaetomium were positively correlated with NO3−–N, NH4+–N, available K, available P, sucrase, and catalase in microbial communities, whereas Aeromicrobium and Mortierella were positively correlated with soil organic matter and urease. These results suggest that T. harzianum biofertilizer could significantly improve the yield and quality of radix bupleuri by changing the structure of soil microbial flora and soil enzyme activity. Therefore, it could be recommended for commercial scale production of Bupleurum.